Synthesis of bioinspired ice-templated bulk metallic glass-alumina composites with intertwined dendritic structure. (November 2019) - Lee, Je In; Wat, Amy; Kim, Jinyeon; Ryu, Chae Woo; Chang, Hye Jung; Park, Eun Soo; Ritchie, Robert O.
Abstract: We have successfully developed bulk-metallic glass (BMG) composites reinforced with intertwined dendritic alumina, inspired by the structure of nacre (Abalone shells). We harness the dendritic growth of ice crystals in a thermal gradient to assemble an alumina with dendritic pore architecture, which is then infiltrated with BMG-forming melt to make a bioinspired, micrometer-scale, intertwined BMG-alumina composite. The composite exhibits ultra-high strength with exceptional relative compressive strength, far better than ceramic particulate BMG composites. The method presented here can be further exploited to produce novel BMG composites with excellent mechanical properties. Graphical abstract: Unlabelled Image